Pelatihan Pembuatan Paving dan Fermentasi Pakan Ternak di Desa Banyoneng Laok Geger Bangkalan dengan Metode Participatory Action Reseach (PAR) - Takwallo Takwallo; Samaun, Samaun; M. Inul Risky (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Banyoneng Laok Village, Geger District, Bangkalan Regency, has great potential to be improved both in the human resources and natural resources sectors, in the human resources sector, many village residents have received education up to high school level and even college, while in the natural resources sector, the majority of residents earn a living as farmers and livestock breeders, but when the dry season arrives they experience difficulties both as farmers and as livestock breeders in meeting their daily needs so that some residents have to choose to migrate out of town or even abroad. The purpose of this community service is to provide education and practice in making pavin and fermenting animal feed to overcome these problems. The method used in this service is participatory action research (PAR) for a full month at the service partner of Banyoneng Laok Village, Geger District, Bangkalan Regency, by directly engaging with the local community. The results of this service are that the community can make their own faving and become a side income and also the community can process animal feed to be more durable and of high quality by fermentation in order to meet the need for animal feed during the dry season.